Dietary Pattern Score, Diet Quality, and Major Neurodegenerative Diseases: A Meta-analysis of Observational Cohort Studies (OR33-07-19). (13th June 2019) - Liu, Yi-Hsuan; Gao, Xiang; Na, Muzi; Kris-Etherton, Penny; Mitchell, Diane; Jensen, Gordon
Abstract: Objectives: Diet is an important lifestyle factor that may prevent or slow the onset and progression of neurodegeneration. Recent studies suggest that adherence to a healthy dietary pattern is associated with reduced risk of cognitive decline. Few studies have examined the relationships between dietary patterns and risk of clinical neurodegenerative disease outcomes. In this meta-analysis, we examined the associations between overall dietary patterns, assessed a priori and a posteriori, and risk of major neurodegenerative disease including dementia, Alzheimer's disease, and Parkinson's disease. Methods: We systematically searched in the PubMed, Web of Science, and Cumulative Index for Nursing and Allied Health databases starting from 1981 to October 10, 2018. Observational cohort studies published in English with prospective and case-control designs were included. Diet assessment approaches (a priori or a posteriori) were utilized to assist in determining whether the exposure was dietary pattern score or diet quality. Generic inverse variance method was used to calculate the pooled risk ratios and 95% confidence intervals (CIs) among the highest versus the lowest diet quality/dietary pattern score groups in random effect models. Results: Seventeen studies with 173, 283 participants were identified. Various diet quality indexes or dietary pattern scores, such as the Healthy Eating Index, the Mediterranean diet score, and dietary pattern scores generated by principal component analysis or reduced rank regression, were used among studies. Our meta-analysis of cohorts showed significant associations between adherence to high diet quality or healthy dietary pattern and lower risk of dementia (pooled risk ratio = 0.70; 95% CI: 0.56-0.86) and Parkinson's disease (pooled risk ratio = 0.72; 95% CI: 0.54-0.97) relative to those with low diet quality or unhealthy dietary pattern. Conclusions: Adherence to high diet quality or healthy dietary pattern may provide protective effects on risk of neurodegenerative diseases. Additional observational studies and randomized controlled trials are needed to address our study limitations and provide further evidence about the role of a poor diet on the development and progression of neurodegenerative diseases as well as the benefits of a healthy diet on the prevention of major neurodegenerative diseases. Funding Sources: United States Department of Agriculture, Agricultural Research Service agreement. Supporting Tables, Images and/or Graphs: